Bridging the Gap: Investigating the Role of Social Workers in Supporting Metastatic Breast Cancer Patients in Nigeria. Issue 3 (3rd April 2022) - Agha, Agha Ali; Onalu, Chinyere; Chidebe, Runcie
ABSTRACT: Cancer is a disease common in every country around the globe with high incidences and deaths. Receiving a breast cancer diagnosis is often associated with a death sentence which makes the individual exhibit self-denial attributes, mixed negative emotions, depression, and anxiety. This study investigated the gap in supportive care and the role of social workers in the management of metastatic breast cancer patients in Nigeria. This study employed a qualitative method using Key Informant Interviews (KII). A total of 12 healthcare professionals in the area of medical social work, palliative care, and medical oncology were engaged in collecting the required information. The result revealed that social workers play significant roles in every aspect of the cancer care continuum – diagnosis, treatment, reintegration, or palliative care. Social workers help metastatic breast cancer patients in Nigeria, however, there are growing challenges to their roles. Most unskilled professionals often present themselves as social workers who do not meet professional standards or perform the best practice.